The Use of Code-switching in the Iranian Bilingual Classroom and its Impact on Second Language Acquisition: A Case Study - Chabokrow, Razieh (2012)
There has been a widespread interest on the use of L1 in the L2 classroom and scholars have been paying further attention to the concept of code-switching through the past few decades. Code-switching is the alternation of one language to another in speech. This study has investigated the impact of the use of code-switching on bilingual students’ L2 learning, and the reasons that prompt it. Teachers’ perception on the concept of code-switching and its presence in the bilingual classroom has also been examined. This research has been conducted at a bilingual school in Iran. A total of 30 secondary female students and two teachers have participated in this study. Observations, teacher interviews and a student questionnaire have been carried out in this research. The results of this study reveal that students code-switch for both linguistic and social reasons. In other words, code-switching has been suggested to facilitate students in their linguistic skills, as they are enabled to use the L1 when facing problems. Also, from the sociolinguistic perspective, code-switching is proved to assist students in overcoming their fear of speaking in L2. This study suggests that code-switching is beneficial to students’ second language acquisition.